Out at home : a novel - Ripken, Cal, Jr., 1960- (Ripken, Cal, Jr., 1960- Cal Ripken, Jr.'s all-stars., 2016)
Twelve-year-olds Mickey Labriogla and Zach "Zoom" Winslow, rivals on and off the baseball field, must learn to work together as teammates to help the Dulaney Orioles win a regional championship game against Zoom's former team.